2020
DOI: 10.1016/j.molmed.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria–Lysosome Crosstalk: From Physiology to Neurodegeneration

Abstract: Cellular function requires coordination between different organelles and metabolic cues. Mitochondria and lysosomes are essential for cellular metabolism as major contributors of chemical energy and building blocks. It is therefore pivotal for cellular function to coordinate the metabolic roles of mitochondria and lysosomes. However, these organelles do more than metabolism, given their function as fundamental signaling platforms in the cell that regulate many key processes such as autophagy, proliferation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(176 citation statements)
references
References 153 publications
(215 reference statements)
1
174
1
Order By: Relevance
“…& P < 0.05 and && P < 0.01 versus the rapamycin group. triggers program that result in the elimination of the defective mitochondria, first by promoting mitophagy, then by ensuring that the capacity for autophagosome degradation is increased by building more lysosomes (Deus et al, 2020). Our results suggested that H/R stimulation leads to defective mitophagy concurrently with cell injury and death, evidenced as reduced cell viability, increased expression of cleaved caspase 3, and apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…& P < 0.05 and && P < 0.01 versus the rapamycin group. triggers program that result in the elimination of the defective mitochondria, first by promoting mitophagy, then by ensuring that the capacity for autophagosome degradation is increased by building more lysosomes (Deus et al, 2020). Our results suggested that H/R stimulation leads to defective mitophagy concurrently with cell injury and death, evidenced as reduced cell viability, increased expression of cleaved caspase 3, and apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, we consider that mitochondrial fragmentation keeps low metabolism levels to reduce cytotoxicity in MD fibroblasts. Mitochondrial fission promotes clearance of damaged mitochondria through a form of autophagy known as mitophagy [42], whereas perturbation of mitochondrial dynamics has been shown to cause lysosomal dysfunction and autophagy impairment [43], and chronic mitochondrial defects trigger general impairment of autophagy and lysosomes to avoid complete degradation of the mitochondrial network [44,45]. Drp1 knockdown or treatment with bafilomycin A1, an autophagic flux inhibitor, significantly increased the amount of mitochondria in MD fibroblasts (Supplementary Figure S2A-C).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their involvement in the catabolism and subsequent recycling of biomolecules, lysosomes coordinate a broad range of intracellular signaling pathways, ranging from mTOR, AMPK, Calcineurin, AKT and ERK1/2, all of which contribute to cancer progression (19,20). Importantly, lysosomal function is essential for mitochondrial function and homeostasis, consistent with the role of these two organelles in promoting malignancies (21)(22)(23). For instance, the lysosomal biogenesis regulator transcription factor EB (TFEB) is essential for mitochondrial biogenesis, respiratory chain complex activities, and ATP production (24,25), while the endolysosomal Rabs play a central role in mitochondrial oxygen consumption, cytochrome-C release during oxidative stress, and mitophagy (26,27).…”
Section: Introductionmentioning
confidence: 84%